HISTORY OF MUHAMMADIYAH: THE BASIC IDEAS BEHIND ITS FOUNDING AND ITS STRENGTH FOR THE FUTURE - Achmad Anton Rizqika Walikrom; Tabroni Tabroni (Jurnal Konseling Pendidikan Islam, 2026)
The historical work of KH. Ahmad Dahlan in 1923 entitled “Tali Pengikat Hidup Manusia” (The Bond of Human Life) focused on the editorial theme of “leaders of Islamic progress,” which became an ideological term. These internal institutional reasons required Muhammadiyah, as a modernist Islamic organization, to take a stand in solving national and global humanitarian issues with a new civilization-humanitarian strategy such as Islam Berkemajuan (Progressive Islam). Methodology: The historical method was used in writing this research, based on the fact that the study to be discussed is a historical study and the data needed in writing the research comes from the past. Discussion: Muhammadiyah in a global context. Progressive Muhammadiyah must be able to contribute to civilizational dialogue and international cooperation that upholds the values of humanity and justice. Muhammadiyah is expected to become a bridge between the Islamic world and the global community in solving various common problems, such as environmental issues, peace, and human rights.